Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Sektor Property And Real Estate Yang Terdaftar Di Bei Tahun 2020-2024 - Titin Wardaini; Berta Agus Petra; Nila Pratiwi (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine how much influence capital structure, company size, on company value with profitability as an intervening variable in property and real estate sector companies. This study uses quantitative research with sampling using purposive sampling method. The independent variables in this study are capital structure, and company size, while the dependent variable is company value. There are 22 companies as research samples. Data were obtained from the company's financial reports published by each company through its official website using SPSS 26. The results of this study are (1) capital structure partially has a negative and significant effect on profitability, (2) company size partially has a negative and significant effect on profitability, (3) capital structure partially has a positive and significant effect on company value, (4) company size partially has a negative and significant effect on company value, (5) profitability partially has a positive and significant effect on company value, (6) profitability is unable to mediate the effect of capital structure on company value, (7) profitability is unable to mediate the effect of company size on company value.